2017
DOI: 10.5863/1551-6776-22.6.399
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacist Intervention on Electrocardiogram Monitoring of Pediatric Patients on Multiple QTc Interval–Prolonging Medications

Abstract: OBJECTIVESTo determine whether dedicated pharmacy services improve the rate of electrocardiogram (ECG) monitoring in patients at risk for medication-induced QTc interval prolongation. In addition, determine how pediatric institutions currently monitor patients at risk for medication-induced QTc interval prolongation.METHODS A pharmacist-driven monitoring protocol to detect medication-induced QTc interval prolongation was developed using published literature. If patients were prescribed 3 or more medications kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The number of patients with a supratherapeutic INR values during admission decreased by over 50% ( P = .039), and goal INR values were documented more consistently in the medical record ( P < .0001). In another free‐standing pediatric hospital, targeted pharmacist inventions to detect patients at risk for medication‐induced QTc interval prolongation were conducted in 88 patients, which were compared against 42 historic controls . The pharmacist recommended baseline ECG in patients receiving three or more medications known to prolong the QTc interval.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…The number of patients with a supratherapeutic INR values during admission decreased by over 50% ( P = .039), and goal INR values were documented more consistently in the medical record ( P < .0001). In another free‐standing pediatric hospital, targeted pharmacist inventions to detect patients at risk for medication‐induced QTc interval prolongation were conducted in 88 patients, which were compared against 42 historic controls . The pharmacist recommended baseline ECG in patients receiving three or more medications known to prolong the QTc interval.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Yet, low rates of appropriate ECG monitoring have also been identified outside of a pandemic setting. Both Daniel et al 18 and Hutchins et al 19 reported low baseline compliance with QTc monitoring for inpatients receiving QTc‐prolonging drugs at 42% and 47.8%, respectively. Clearly, inadequate QTc monitoring is not a problem unique to this pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…This barrier could also be an area of future research to determine the pervasiveness and impacts of these concerns. Increasing the scope pharmacists' scope has been shown to reduce QTc interval prolongation and increase appropriate ECG utilization [ 2 , 22 , 23 ]. Another barrier that should be considered is that pharmacists typically work with a supervising prescriber who must approve their therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%